Alteration of Effector Activity of T-Lymphocytes in Mice Immunized against Tularemia, Using in vitro Stimulation by Tularin - V. V. Firstova (Проблемы особо опасных инфекций, 2012)
lymphocytes) isolated from mice, immunized against tularemia. Put forward is the proposition to use tularin in serological surveys and reactions in vitro for identification of postinfectious or postvaccinal immunity to tularemia.